2015
DOI: 10.1051/mbcb/2014034
|View full text |Cite
|
Sign up to set email alerts
|

Rééducation fonctionnelle des troubles musculo-squelettiques de l’appareil manducateur : de ses principes biologiques à la clinique (4e partie)

Abstract: Introduction : Dans les troubles musculo-squelettiques (TMS), les effets biologiques de la rééducation fonctionnelle sont en cours d'évaluation. Discussion : Elle entraîne des modifications motrices. Dans les cervicalgies, elle augmente l'activité agoniste, diminue les activités synergistes compensatoires et l'activité antagoniste, et a priori améliore les régulations anticipatoires. De plus, la rééducation induit des modifications neuroplastiques au sein de l'aire motrice M1. On suppose que la rééducation vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Recent clinical studies demonstrated the biological effects of physiotherapy in musculoskeletal disorders (non-specific low back and neck pain) and suggested hypotheses 14 . Likewise, pioneering studies showed that tongue exercises incrowding, tongue/palate exteroception is vitiated, preventing correction becoming reflex.…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies demonstrated the biological effects of physiotherapy in musculoskeletal disorders (non-specific low back and neck pain) and suggested hypotheses 14 . Likewise, pioneering studies showed that tongue exercises incrowding, tongue/palate exteroception is vitiated, preventing correction becoming reflex.…”
Section: Resultsmentioning
confidence: 99%
“…Récemment, des études cliniques ont objectivé les effets biologiques de la kinésithérapie dans les troubles musculo-squelettiques (lombalgies et cervicalgies non spécifiques) et des hypothèses ont été proposées 14 . De même des études pionnières ont démontré que des exercices de langue entraînaient des modifications neuroplastiques au niveau du cortex moteur primaire (M1) des muscles de langue se traduisant par un accroissement de l'excitabilité des motoneurones cortico-bulbaires et de la taille de l'aire motrice des muscles linguaux ( fig.…”
Section: Resultsunclassified
“…Conversely, during a lower lingual posture and immature tongue function, the activity of the platysma muscles predominates over that of the masticatory muscles. however, in the current state of clinical knowledge, we do not know the phenomena possibly implicated in lingual and maxillofacial rehabilitation in general as this is a new field of research [8][9][10] .…”
Section: Limits Of Rehabilitation Standardized Tongue Exercisesmentioning
confidence: 97%